KRITERIA 29: CARA PANDANG BARU DALAM PENYUSUNAN KALENDER HIJRIYAH - Setyanto, Hendro; Hamdani, Fahmi Fatwa Rosyadi Satria (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2015)
HilÄl is an early marker of the beginning of the Hijriyah/Qamariyah. The existence of the new moon was used as a reference in the preparation of a system of Islamic calendar. The issue of the new moon it is still be an interesting thing to be studied. In fact there is a lot of research and discussion related with hilÄl issues. However, it still has not found an appropriate formula to be used as a reference in creating a standardized system of the Islamic calendar. Currently, there are several criteria that offered to make the calendar system. In this paper, will be presented criteria and other perspectives in formulating a Hijriyah calendar, called the Criteria 29. Some examples of simple calculations and discussions in determining the first day of month of the Hijriyah presented briefly. This elaboration of â€œCriteria 29â€ hopefully can give an idea and different viewpoints in order to develop Hijriyah calendar.